R.M. Schindler - Sheine, Judith; Schindler, R. M.; Mudford, Grant (London ; New York : Phaidon, 2001)
Foreword Introduction Chapter 1: Getting to Los Angeles or Famous Architects He Knew Chapter 2: Schindler and Wright or The First Space Architect Chapter 3: Schindler and The International Style or His Work Had No Place in It: Modern Architecture: A Program Chapter 4: Theory or Space, Climate, Light, Mood Chapter 5: The Early Years or Concrete and Radicalism Chapter 6: Plaster-Skin Design or The Search for Cheapness Chapter 7: The Search for Form or "There is Certainly Immense Vitality..." Chapter 8: The Late Work or The Schindler Frame and Visual Techniques Chapter 9: Practice or R.M. Schindler, Architect Chapter 10: Influence and Reputation or He Was an Incorrigible Bohemian Chapter 11: Conclusion or I, in Common with Many Others, Like Him Very Much Notes Works and Projects Selected Bibliography Index
Includes bibliographical references (p. 295-299) and index.
boek
Keywords: Schindler, R. M